EFFECTIVENESS THE OINTMENT OF FOREST BETEL LEAVES EXTRACT (Piper aduncum L. ) AGAINST EXCISION WOUNDS - Diza Sartika; Ria Afrianti; Rihadhatul Aisy; Miftahur Rahmi (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2024)
Excision wounds are included in open wounds and occupy the top three types of injuries experienced by the public. Forest betel (Piper aduncum L) is one of the plants that can be used in healing excision wounds because it contains several chemical ingredients such as flavonoids, steroids and saponins which can help speed up wound healing. This study aims to determine the effectiveness of ointment extracts of forest betel leaves (Piper aduncum L.) on the healing of excision wounds in male albino rats. Animals are divided into 5 groups there are control group (base used of vaselinflavum ointment), group of forest betel leaf extract concentration 5%, 10%, 15% and the comparison group (Ointment T®). Basting of preparation was done twice a day for 21 days. The parameters observed were the percentage of wound healing, epithelialization time and histopathology. The results showed on the average percentage of excision wound healing on the 7th, 14th and 21st days were control group ( 43.046% , 84.118%, 92.866% ), concentration 5% (45.49%, 87 608%, 94.704%), concentration of 10% (46.196%, 88.24%, 96.692%), concentration of 15% (46.572%, 91.058%, 97.886%) and the comparison group (46.572%, 90.01%, 97.372%). the control group (8 days), 5% concentration (7 days), 10% concentration (6.8 days), 15% concentration (6.4 days) and the comparison group (6.6 days).For the histopathological test, the results of epithelialization, collagen fiber, and fibroblast scores were. respectively the control group (2,2,1), 5% concentration (2,2,2), 10% concentration (2,2,2), 15% concentration (3,3,3) and the comparison group (3 ,3,3). The most effective group for excision wound healing was the 15% concentration group.